Latent Tuberculosis Infection among Children under Five Years - Ameer, Hira; Moorani, Khemchand N; Parkash, Arit; Anjum, Misbah; Sameen, Ifra (Infectious Diseases Journal of Pakistan, 2023)
Background: Latent tuberculosis infection (LTBI) is a significant public health problem. Despite the advanced diagnostic tools, the LTBI remains undiagnosed. Objectives: To determine the frequency of LTBI and its predisposing factors in children under 5 years. Methods: This cross sectional study was conducted in Out Patient Department (OPD) of National Institute of Child Health (NICH), Karachi from March 2014 to September 2014 after informed parental consent. All children under 5 year who attended OPD with symptoms like fever, cough of less than one week were screened. Children with strong suspicious of Tuberculosis (TB) were excluded. Medical factors contributing to LTBI such as family history of tuberculosis, BCG vaccination status and malnutrition on assessment were noted. Social factors including lack of parental education, passive smoking and overcrowding were also noted. All included children were given tuberculin skin test (TST) and an induration of 10 mm was considered positive TST. Results: A total of 443 children were screened for LTBI during study period. Children’s mean age was 3.40 ±0.96 years. Illiteracy (88%), passive smoking (65%) and over crowding (24%) were social factors where as malnutrition (53%), positive family history (35%) and lack of BCG vaccination (71%) were medical factors found among screened children. LTBI was strongly correlated with age, weight, nutritional status and passive smoking (p-value <0.05). Conclusion: LTBI was found in 3.83% of screened children with important contributing factors of illiteracy, passive smoking, malnutrition and TB in family. Key words: Latent Tuberculosis Infection, illiteracy, passive smoking, malnutrition